A comparative study between heterogeneous stannous chloride loaded silica nanoparticles and a homogeneous stannous chloride catalyst in the synthesis of 5-substituted 1H-tetrazole. Issue 79 (8th August 2016) - Kumar, Arvind; Kumar, Satyanand; Khajuria, Yugal; Awasthi, Satish Kumar
Abstract : Heterogeneous SnCl2 –nano-SiO2 efficiently catalyzed 5-substituted 1 H -tetrazole synthesis with excellent yield. It is widely applicable on aliphatic, aromatic, heteroaromatic and sterically hindered nitriles with five times recyclability. ​ Abstract : Heterogeneous SnCl2 –nano-SiO2 efficiently catalyzed 5-substituted 1 H -tetrazole synthesis with excellent yield. The catalyst was characterized by using FT-IR, TGA, TEM, and EDX. It is widely applicable on aliphatic, aromatic, heteroaromatic and sterically hindered nitriles with five time recyclability. Being simple and an economically viable approach for the synthesis of SnCl2 –nano-SiO2 are additional advantages.